Landak Industrial Park (LIP) Development Strategy - Sagala, Tanty N. J.; Surjono; Antariksa; Sari, Indah Cahayaning; Dzvimbo, Munyaradzi Admire; LeaBarrett, Janine (Civil and Environmental Science Journal (CIVENSE), 2023)
Landak Industrial Park (KIL; Kawasan Industri Landak) is a national strategic project for Industrial Estates in West Kalimantan and is included in the List of 14 Priority Industrial Estate Developments Outside Java Island in the 2020-2024 National Medium-Term Development Plan (RPJMN; Rencana Pembangunan Jangka Menengah Nasional). The construction of KIL is experiencing delays, and to prevent the project from stalling, the main sources of industrial growth are new investment and increased utility from the current capacity. This study’s approach is both qualitative and quantitative. The analysis technique used is SWOT analysis using Internal Strategic Factor Analysis Summary (IFAS) and External Strategic Factor Analysis Summary  (EFAS), developed using spatial analysis techniques from the concept of economic aggregation, which then generates value propositions and makes them the basis of a marketing strategy that includes market segmentation (segmenting), setting market targets (targeting), and creating a unique position (positioning). The result is from the SWOT analysis. KIL is in the turnaround quadrant, a position with a strategy of maximizing opportunities because it has major internal weaknesses. The geographical reach of other economic groups or business clusters that are quite close together is a trigger for the development of KIL. Scenarios from the KIL development strategy are expected to support strategic business decisions.